MENELISIK METODOLOGI HISAB-RUKYAT DI INDONESIA - Sakirman Sakirman (Hunafa: Jurnal Studia Islamika, 2011)
This paper deals with the significance of the methods of calculation (ḥisāb) and observation (ru’yah) in determining the beginning of month in Islamic calendar, especially months of  Ramaḍān, Shawwāl and Żū al-Ḥijjah, since these months have relationship with sacred Islamic rituals. However, Muslims should review and reexamine the basic method employed in determining  beginning of month in Islamic calendar. Classical dichotomy that has led to controversy until these days relates to ḥisāb and ru’yah. Some said that ru’yah method is final and decisive while ḥisāb is only supporting ru’yah. Others said that it is ḥisāb that is final and decisive, while ru’yah is used to support the method of ḥisāb. From this dispute, there should be a meeting point; that is, ru’yah should be supported by accurate science of ḥisāb.